2007
DOI: 10.1097/mcc.0b013e3280895d5c
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in traumatic brain injury: a complex struggle against the biology of nature

Abstract: Traumatic brain injury is a complex disease, and development of clinically effective neuroprotective agents is a difficult task. Experimental traumatic brain injury has provided numerous promising compounds, but to date these have not been translated into successful clinical trials. Continued research efforts are required to identify and test new neuroprotective agents, to develop a better understanding of the sequential activity of pathophysiologic mechanisms, and to improve the design and analysis of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 65 publications
0
87
0
4
Order By: Relevance
“…The etiology of secondary brain injury is multi-factorial, with a host of likely inter-related processes including mitochondrial energy failure; excessive generation of reactive oxygen species; activation of destructive enzymes such as poly (ADP-ribose) polymerase (PARP), and the caspase family of proteases; membrane disruption; neuronal death; thrombosis caused by intravascular coagulation in small vessels; increased synaptic concentrations of excitatory amino acids; and activation of innate inflammatory responses (Schouten, 2007). Several reviews have suggested the need for pharmacological treatments that target multiple secondary factors, or combination treatment strategies (Faden and Stoica, 2007;Schouten, 2007).…”
Section: T He Centers For Disease Control and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of secondary brain injury is multi-factorial, with a host of likely inter-related processes including mitochondrial energy failure; excessive generation of reactive oxygen species; activation of destructive enzymes such as poly (ADP-ribose) polymerase (PARP), and the caspase family of proteases; membrane disruption; neuronal death; thrombosis caused by intravascular coagulation in small vessels; increased synaptic concentrations of excitatory amino acids; and activation of innate inflammatory responses (Schouten, 2007). Several reviews have suggested the need for pharmacological treatments that target multiple secondary factors, or combination treatment strategies (Faden and Stoica, 2007;Schouten, 2007).…”
Section: T He Centers For Disease Control and Preventionmentioning
confidence: 99%
“…Several reviews have suggested the need for pharmacological treatments that target multiple secondary factors, or combination treatment strategies (Faden and Stoica, 2007;Schouten, 2007).…”
Section: T He Centers For Disease Control and Preventionmentioning
confidence: 99%
“…La neuroprotección intenta bloquear las cascadas fisiopatológicas que desembocan en el daño cerebral secundario, así como contribuir a la reparación del sistema nervioso central 17 .…”
Section: Neuroprotecciónunclassified
“…The resulting complex gene expression profiles obtained from these heterogeneous tissues, and the often conflicting patterns of injury-induced cellular signals, may be one explanation for the failure in human clinical trials of therapeutic strategies proven effective in pre-clinical studies of TBI. 5 To obtain a clear understanding of injury-induced gene expression in vulnerable populations of neurons from the rat hippocampus, we adopted the technique of LCM, first reported by Emmert-Buck et al 3 Subsequently, we modified and optimized this microdissection technique for efficient capture of enriched populations of neurons and single neurons for mRNA profiling using quantitative real time PCR and microarray analysis. To maintain the integrity of mRNA in frozen sections of brain tissue for genomic analysis, we modified existing protocols for fixing, staining and rapid capture of neurons from frozen rat brain sections.…”
Section: Introductionmentioning
confidence: 99%